The Quality of the Food Retail Environment When Consumers May Be Mobile. Issue 2 (1st February 2021) - Wilde, Parke; Ismail, Mehreen; Ver Ploeg, Michele
Abstract: Using USDA's National Household Food Acquisition and Purchase Survey (FoodAPS), we estimated block group‐level spending‐weighted mean distance to the retailers where consumers actually shop (3.9 miles overall; 7.0 miles in rural areas and 3.0 miles in urban areas). Holding constant retailer type, every 10% increase in travel distance was associated with a 3.5% decrease in the food‐at‐home spending share. If consumers travel farther to get food, it may signal that they lack satisfactory options at closer distances. Spending‐weighted mean travel distance could support measures of food retail gaps that are consistent both with consumers' revealed preferences and retailers' incentives.